MICRO AND CRYSTAL STRUCTURE ANALYSIS OF NEW AUSTENITIC STEEL. - Nurdin Effendi (Jurnal Sains Materi Indonesia, 2010)
MICRO AND CRYSTAL STRUCTURE ANALYSIS OF NEW AUSTENITIC STEEL. New austenitic stainless steel code-named A1 has been synthesized using the foundry method. The steel was prepared from the crude minerals mined in Indonesia consisting of ferro scrap, ferro chrome, ferro mangan, and ferro silicon; all of them were in the granular shape. Moreover, a small quantity of titanium was added to this austenitic steel that already has a very low carbon content. The synthesis was started by calculating each raw material quantity from the given specification data with the material balance equation, so that the austenitic composition specification matches the originally conceived specifications. After all of the crude material quantities were determined, each of the crude materials to be used in the alloying process were then weighed separately. The process was continued by inserting the crude materials into an induction foundry furnace that operates on an electromagnetic inducto-thermo system. The stirring was carried out automatically by the system. The now homogenous melting materials were then inserted into the ladle, followed by pouring into the sand casting. Some of the steels was normalized by a homogenization process at 1200 oC for 20 hours, and additional characterization was carried out afterwards. The microstructure observation shows that the material surface is relatively homogenous but with some porous holes. The X-ray diffraction pattern shows that the material had a fcc crystal structure with lattice parameter of 3.564 Å.